2011
DOI: 10.1159/000322666
|View full text |Cite
|
Sign up to set email alerts
|

Anemia, Iron Deficiency and Thalassemia among Adolescents in Northeast Thailand: Results from Two Independent Surveys

Abstract: The prevalence of adolescent anemia, iron deficiency and thalassemia were examined in 2 provinces of northeast Thailand. Blood specimens were collected from adolescent subjects aged 15–17 years in 2 areas; 185 (85 males and 100 females) in Mukdahan province and 313 (116 males and 197 females) in Roi-Et. RBC parameters, serum ferritin levels, Hb and DNA analyses for the identification of common thalassemia genes in Thailand were investigated. The prevalences of anemia were found to be 21.1% (8.1 in male and 13.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 48 publications
5
20
2
Order By: Relevance
“…A recent study conducted in Vietnamese children and nonpregnant women revealed results similar to those of this study, with markedly reduced prevalences of anemia, ID, and IDA [20]. Similar findings were also obtained in many studies conducted in Thailand in that the prevalence of IDA was not high [29,30,31,32]. The outcomes of the studies indicate that the burden of anemia due to ID in the region has improved.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A recent study conducted in Vietnamese children and nonpregnant women revealed results similar to those of this study, with markedly reduced prevalences of anemia, ID, and IDA [20]. Similar findings were also obtained in many studies conducted in Thailand in that the prevalence of IDA was not high [29,30,31,32]. The outcomes of the studies indicate that the burden of anemia due to ID in the region has improved.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies conducted in Northeast Thailand have demonstrated that anemia in the region is associated with thalassemia and hemoglobinopathies rather than ID [29,30,31,32]. This seems not to be the case in Vietnam since the prevalence of the 3 clinically significant thalassemias is relatively lower.…”
Section: Discussionmentioning
confidence: 99%
“…While the proportion of thalassemia in the vegans is similar to the autochthonous population, as has been reported previously [17,18,19,20], the proportion of anemia, ID and IDA in the group of vegans is higher than in the general population within the area of northeast Thailand. The findings confirm the increased risk for individuals who are dedicated to a vegan lifestyle and this underlines the need to prevent and control IDA in this specific population.…”
Section: Discussionsupporting
confidence: 84%
“…For IDA, a prevalence range of 1–18% has been reported in pregnant women and school children [17,18,19,20]. There have been no reports for vegetarians.…”
Section: Introductionmentioning
confidence: 99%
“…Thalassemia is the most common hematologic disease in Thailand [1,2]. Treatment of thalassemia, which including regular blood transfusion and iron chelation therapy have improved quality of life of these patients and increased their longevity.…”
Section: Brief Communication (Original)mentioning
confidence: 99%